THE ANALYSIS OF THE USE OF COMMUNICATION TECHNOLOGY TO THE EFFECTIVENESS OF INTERNAL COMMUNICATION - Adam, Evants; Kartikawangi, Dorien (Jurnal InterAct, 2018)
In this digital era, the development of Information and Communication Technology has changed the way people communicate. Marked by the booming of smartphone in previous years, ICT quickly becomes a trend is both daily and work life. It is also created a new way for organization to convey it messages. This study discusses about that matter. Based on qualitative methods, this research covering about the utilization of Instant Messenger and Video Conference in Internal Communication at SIBBC Consulting Organization, a Swiss-based consulting organization. The aim of this research to look and gain a deeper insight about the uses of ICT. The theories used as a basis are organizational communication, internal communication, information and communication technology, and the effectiveness of communication. The data collected by doing an indepth interview to five (5) subjects and observation results by the writer. The study finds that the use of Instant Messenger and Video Conference for internal communication were assessed positively and able to facilitate the needs of communication in the organization. The challenges in this study was the difficulties to reach the manager-level to get their in-depth feedback for the use of the ICT.